(untitled) (Acta Scientiarum. Animal Sciences, 2019)
The aim of this study was to determine the effects of supplementing close-up and fresh dairy cows’ diets with sodium selenite or organic sources of selenium (Se) on the serum biochemical parameters and antioxidant indicators and Se status. Twenty-four multiparous Holstein dairy cows were balanced by body condition score (BCS), previous lactation milk yield and expected calving date and randomly assigned to 1 of 4 experimental treatments. Treatments were: control (basal diet without Se supplementation), sodium selenite supplementation (0.50 mg of Se kg-1 DM; Se-S), selenium yeast supplementation (0.50 mg of Se kg-1 DM; Se-Y) and selenomethionine supplementation (0.50 mg of Se kg-1 DM; Se-M). Serum Se concentrations were higher for cows in Se-Y (72.34 µg dL-1) and Se-Met (72.34 µg dL-1) than control (59.93µg/dl) and Se-S (64.79µg/dl). The Se supplementation and sources did not affect serum metabolites or indices of antioxidant pre and postpartum, except serum total protein and albumin concentrations. Cows in Se-M had greater serum total protein and albumin concentrations than those in control. The results of present study showed that serum Se concentrations increased in Se-Y and Se–M more effectively than Se-S, indicating that selenomethionine could replace Se-S as an effective organic Se source for transition dairy cows.